Large mediastinal teratoma associated with severe pleural pericardial stroke due to perforation of both structures - Carlos Manuel Angulo Elers; Sorangel Bolaños Vaillant; Emilio Urgellés Angulo (Centro Provincial de Información de Ciencias Médicas, 2017)
The case report of a 21 years patient is presented who is admitted in the Cardiology Service of "Saturnino Lora Torres"TeachingClinicalSurgicalProvincialHospitaldue to acute pericarditis of torpid course. When the computerized axial tomography of the mediastinal cavity was carried out, a teratoma associated with severe pleural pericardial stroke due to rupture of both structures was diagnosed. He was treated with extracorporeal circulation and the histologic diagnosis was confirmed.